Sistem Pengendali Alat Elektronik Rumah Tangga Berbasis Internet of Things (IoT) Menggunakan Voice Recognition - Haeruddin, Haeruddin (Journal of System and Computer Engineering, 2024)
Using switches on household electronic devices that use electrical energy requires human action to get to the switch location and requires more time and energy. If human conditions do not allow for physical activity, such as for people with disabilities or people who are tired or sick, this is very difficult to do. The aim of this research is to create a system for controlling the use of household electronic devices based on the Internet of Things (IoT) using Voice recognition. This research was conducted at the Malone Celuler Shop in Bulukumba Regency. This type of research is Research and Development (R&D) with 6 stages, namely literature study and problem formulation, problem analysis, data collection, system design, system design implementation and system testing. The instruments used in this research were a laptop, Arduino Uno, PZEM-004T sensor, blynk application, voice recognition. The research results show that the system for controlling the use of household electronic equipment can turn it off and on effectively through voice recognition and provide information on whether household electronic equipment is still on when outside the home with the blynk application